The Effect of Career Development and Training on Organizational Performance : the Mediation Role of Employee Competence - M Ryan Alvarezy; Ani Jamiyati; Trisno Ajisantoso Bagusromadhan; Pupung Purnamasari (LPPPIPublishing, 2025)
This study aims to analyze the influence of Career Development and Training on Organizational Performance with Employee Competence as a mediating variable. In the context of a dynamic business environment, the role of employee competence is crucial in transforming Human Resources (HR) initiatives into tangible company performance. Data was obtained through in-depth interviews with a number of employees from various levels of positions. The results show that Employee Competence has a positive and significant effect on Organizational Performance. Furthermore, Training was found to have an influence on Organizational Performance only indirectly, proving Full Mediation by Employee Competence. Meanwhile, Career Development showed a dual influence, namely direct and indirect, indicating Partial Mediation. These findings underscore the importance of HR strategies that focus on competency improvement outcomes as a primary prerequisite for investments in training and career development to contribute optimally to organizational performance.